Kazakhstan television on online (Herald of Journalism, 2018)
This article discusses the development of process in the Kazakh television sector during the technological progress. Traditional television service broadcasting is not the only way to provide information to the public. The Internet has expanded the horizons of broadcasting capacity at times in scope and speed. In this article we looked at the practice of using the Internet space and broadcast on-line, presented a table, defined scale of using of Internet resources. And relying on the research work of Western researchers about the process of convergence and new media capabilities, we sought to determine the development of the Kazakh media. New technological possibilities raise new media opportunities.
Keywords: Key words: television, technological progress, journalism, new media, traditional media, online, convergence.